Iron(II) chloride enhances the biocontrol activity of Pseudomonas fluorescens against root-knot nematodes - ANKARDIANSYAH PANDU PRADANA; MOHAMMAD HOESAIN; IIS NUR ASYIAH; MUH ADIWENA; YELVI ANGELINA; DIANA PUTRI; RACHMI MASNILAH; RIFANI RUSIANA DEWI (Society for Indonesian Biodiversity, 2025)
Abstract. Pradana AP, Hoesain M, Asyiah IN, Adiwena M, Angelina Y, Putri D, Masnilah R, Dewi RR. 2025. Iron(II) chloride enhances the biocontrol activity of Pseudomonas fluorescens against root-knot nematodes. Biodiversitas 26: 4243-4256. Root-knot nematodes (Meloidogyne incognita) account for over 15% of global crop losses, highlighting the urgent need for sustainable biocontrol solutions. Microbial-based strategies, particularly those employing Pseudomonas fluorescens, present environmentally responsible alternatives to chemical nematicides while enhancing soil microbial diversity. The aim of this study was to evuluate the systematic assessment of Iron(II) Chloride (FeCl?) supplementation for improving the nematicidal efficacy of P. fluorescens. Five treatment combinations of FeCl? (0, 50, and 75 ppm) and pH (6 and 8) were evaluated in vitro. The results showed that at 24 hours, J2 mortality reached 16.8% in the 75 ppm FeCl? treatments (pH 6 and 8), significantly exceeding the control (4.4%, p<0.05). By 96 hours, FeCl?-fortified cultures achieved 55.6-56.4% J2 mortality, compared to 35.0% in the control (p<0.05). At 168 hours, maximum J2 mortality of 97.0% was recorded with 75 ppm FeCl? at pH 8, nearly three times higher than the control (p<0.01). Similarly, inhibition of egg hatching was markedly enhanced; after 168 hours, 82.8% of eggs remained unhatched in the 50 ppm FeCl? at pH 6 treatment, versus 29.8% in the control (p<0.01). Gas Chromatography-Mass Spectrometry analysis revealed a significant increase in bioactive fatty acid derivatives, such as methyl linoleate, in FeCl?-supplemented cultures, supporting a mechanism of nematode membrane disruption. Collectively, these findings demonstrated that FeCl? supplementation significantly enhances the nematicidal activity of P. fluorescens, offering a novel and effective strategy for sustainable management of root-knot nematodes. This approach offers considerable potential for integration into environmentally compatible crop protection strategies, contributing to the development of sustainable nematode management practices in agricultural systems.